Beneficial effect of Hypericum perforatum on depression and anxiety in a type 2 diabetic rat model - Husain G.M.; Chatterjee S.S.; Singh P.N.; Kumar V. (My University, 2025)
Recent studies have revealed diverse therapeutically interesting pharmacological properties of a standardized Hypericum perforatum extract (HpE) potentially useful for treatments of patients with metabolic and psychiatric disorders. Consequently, the presented experiments were designed to test usefulness of the extract for the treatment of comorbid conditions of mood disturbances and anxiety in diabetic rats. Type 2 diabetes mellitus was induced in overnight fasted rats by a single i.p. injection of streptozotocin (STZ; 65 mg/kg), 15 min after an i.p. injection of nicotinamide (120 mg/kg). HpE was administered orally (100 and 200 mg/kg b.w..) to diabetic animals for 14 days. Anxiolytic activity was evaluated using open-field exploration test (OFT) and elevated plus maze (EPM) test. Antidepressant activity was assessed using Porsolt's forced swim test (FST). Fasting blood glucose levels in different groups were analyzed on the 14th day. Diabetic rats showed significant increase in anxiety in OFT and EPM compared to non diabetic normal control rats. Diabetic rats treated with HpE have shown significant anxiolytic activity in OFT and EPM test. In FST, immobility period of vehicle treated diabetic rats was significantly increased (p < 0.05) compared to normal control rats. Treatment with HpE significantly decreased (p < 0.001) immobility period compared to vehicle treated diabetic control rats. HpE treatment significantly reduced elevated blood glucose levels in diabetic rats. The presented observations strongly suggest that HpE could be suitable alternative therapeutic option for prevention, as well as treatment, of comorbidities caused by, or associated with, depression, anxiety and diabetes.